Wrist Salvage and Fusion Outcomes in a Veterans Affairs Population - Lawson, Edward; Cinclair, Trey; Lies, Shelby (Journal of Wrist Surgery, 2024)
Introduction Wrist osteoarthritis (OA) is a common condition in the elderly population that can lead to significant impairment. Common causes of wrist OA are scapholunate advanced collapse (SLAC) and scaphoid nonunion advanced collapse (SNAC). This study examines the outcomes of wrist salvage and fusion surgeries in the treatment of posttraumatic wrist arthritis caused by SLAC/SNAC in the Veteran population.Materials and Methods A retrospective review was performed of patients who presented to a single Veteran Affairs hospital with wrist arthritis over the period of 12 years. Information analyzed included patient demographics, SNAC/SLAC grade, and first operation (proximal row carpectomy, four-corner fusion, and total wrist fusion). Outcomes reviewed included postoperative malunion, impingement, hardware failure, postoperative range of motion (ROM), persistent pain, recurrent arthritis, and need for reoperation.Results In the proximal row carpectomy group, 11 (29%) patients had poor ROM postoperation, 14 (36.8%) had persistent pain, 3 (7.9%) had recurrent arthritis, and 2 (5.3%) needed reoperations. In the four corner fusion 4CF group, 3 (13.6%) patients had malunion, 3 (13.6%) had impingement, 5 (22.7%) had a hardware failure, 2 (8.7%) had poor ROM postop, 9 (40.9%) had persistent pain, 6 (27.3%) had recurrent arthritis, and 6 (27.3%) needed reoperations. In the total wrist fusion TWF group, 2 (18.2%) patients had malunion, 2 (18.2%) had impingement, and 2 (18.2%) had hardware failure. No patients had poor ROM postoperation, 5 (45.5%) had persistent pain, 2 (18.2%) had recurrent arthritis, and 3 (27.3%) needed reoperations.Conclusion In the treatment of wrist arthritis, partial wrist fusions are optimal for maintaining ROM while improving pain control.Level of Evidence III
Keywords: wrist arthritis; proximal row carpectomy; four corner fusion; total wrist fusion